The Language of Mediums and Healers in the Spiritualist Church - Tschanz, Linda (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1981)
Spiritualism focuses on two levels of existence: life on earth and life in the spirit world. These two worlds are brought into contact through the psychic abilities of mediums. The language of mediums relies on nineteenth century imagery to convey Spiritualist values about work, spiritual advancement, and communication with the spirit world. This paper is an examination of some of the terms which convey and condense the theology and values of Spiritualism.